Muscles, Nerves, and Pain : A Guide to Diagnosis, Pain Concepts, and Therapy - Nix, Wilfred A. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
Many patients suffer from problems in their muscles or nerves in combination with pain. This book is about the complex interplay between the causes of these problems and the puzzle they pose. Pain is the subjective experience of a psychophysical phenomenon arising from a defined area in the body. It is a cry for help and challenges the physician to ask the right questions and to carry out the right examinations. If they succeed in doing so, the patient's signs and symptoms will be translated into the present knowledge of pain concepts to initiate appropriate therapy. With this goal in mind, this book summarizes the latest scientific information on pain states and their mechanisms. It provides a deeper understanding of the different pain conditions and allows physicians to form strategies for better pain therapy. The second edition includes more graphs, tables, and illustrations. It is updated with the current and dynamically expanding knowledge on the therapy of several disease states and explains in more detail the processing of pain in the central nervous system. When puzzling symptoms of sensory, motor, and autonomic deficits are evident, an examination has to be performed systematically in order to reach the correct diagnosis. This calls for suitable anatomical knowledge. Depending on where a lesion exists within a peripheral nerve, the root or the plexus, typical patterns of paralysis can be detected. Numerous illustrations in the book help physicians to more easily understand and solve problems of peripheral nerve and root injuries and their sequelae in their daily work. .
Keywords: Medicine.; Neurology.; Pain medicine.; elektronické knihy; electronic books